Investigating the causal relationship between immune factors and ankylosing spondylitis: insights from a Mendelian Randomization study - Ziming Geng; Yang Tong; Yang Chen; Jian Wang; Ziwen Liu; Jun Miao; Ruihua Li (Advances in Rheumatology)
Abstract Background Despite previous studies indicating a close relationship between immune system and ankylosing spondylitis (AS), the causal relationship between them remains unclear. Methods Genome-wide association data were utilized to explore the causal link between 731 immune cells and AS using a bidirectional two-sample MR approach. The data included immune cell data from Orrù et al.’s study and AS data from the FinnGen consortium. Cochran’s Q test and leave-one-out checked instrument variable (IV) heterogeneity. IVW was the primary method for causal analysis, with MR-Egger and MR-PRESSO addressing horizontal pleiotropy. FDR correction was applied to both analysis directions to rectify multiple testing errors. Results In our study, 22 immune phenotypes out of 731 were casually linked to AS. After excluding 5 less robust features, 17 immune factors remained, with 4 being protective and the rest posing risks. Through FDR correction, we found a significant causal relationship between HLA DR on CD14- CD16+ monocyte and AS (OR (95%CI) = 0.70(0.60 ~ 0.83), P = 2.06*10−5). In the reverse analysis with AS as exposure, potential effects on 34 immune features were discovered. After correction, we confirmed significant causal relationships between AS and two immune features, namely CD20- B cell %lymphocyte (OR (95%CI) = 1.16(1.08–1.25), P = 1.91*10−5) and CD20- B cell %B cell (OR (95%CI) = 1.17(1.09–1.26), P = 1.50*10−5). Conclusions Our study identified various features associated with AS in different types of immune cells. These findings provide important clues and a theoretical basis for further understanding the pathogenesis of AS, guiding clinical treatment, and drug design.